Exclusive Breast Milk with the Risk of Stunting in Incidents Toddlers Aged 24-59 Months: ASI Ekslusif dengan Risiko Kejadian Stunting pada Balita Usia 24-59 Bulan - Olkamien Jesdika Longulo; Muliani Muliani; Mardiani Mangun; Anna Veronica Pont; Susanti Susanti (Poltekkes Kemenkes Palu, 2023)
Background Data in the working area of the Ongka Health Center UPTD Based on Toddlers aged 24-59 months totaled 826 toddlers with 77 stunted toddlers (9.3%). The purpose of this study was to determine the relationship between exclusive breastfeeding and the risk of stunting in toddlers aged 24-59 months in the UPTD Work Area of the Ongka Health Center. Methods Case-control method, the population of all mothers who have toddlers at the Ongka Health Center is 826 toddlers. Sample with a ratio of 1:2, the case group is 77 toddlers who are stunted and the control group is 154 toddlers who are not stunted, the sample size is 77+154 = 231, toddlers. The instrument used is secondary data on the history of exclusive breastfeeding for toddlers. Univariate data analysis using frequency distribution and bivariate with Chi-Square test. The result of the statistical test for the p-value is 0.003 with a significant value of ≤0.05. The conclusion is that there is a relationship between exclusive breastfeeding and the risk of stunting in toddlers aged 24-59 months in the working area of the UPTD Puskesmas Ongka. Health workers are expected to increase the provision of information and attention to the risk factors for exclusive breastfeeding with the incidence of stunting and increase the coverage of exclusive breastfeeding in the work area of the Service Technical Implementation Unit (UPTD) of the Ongka Health Center.